Comparing the Coach-Athlete Relationship between Greece and Cyprus - Ioannou Λεωνίδας; Patsiaouras Αστέριος; Tsoutsoumpi Λυδία; Karakatsani Αναστασία; Soulas Δημήτριος (Inquiries in Physical Education and Sport, 2014)
The purpose of this study was to examine possible differences existing between track and field athletes as regards to the relationship they develop with their coaches referring to the three constructs that determine the dynamics and the quality of the relationship, that is closeness, commitment and complementarily. Participants were 257 athletes and coaches (223 athletes and 34 coaches), from Greece and Cyprus, who completed the Coach-Athlete Relationship Questionnaire (GrCart- Q) by Jowett and Ntoumanis (2003), so as to examine the coach-athlete relationship. Results showed statistically significant differences between Greek and Cy-priot athletes and coaches, with Greek athletes scoring significantly lower than Greek Cypriot athletes in all questionnaire variables. Similar results were noted for Greek coaches as compared to Cypriot ones, for two out of the three factors (closeness and complementarily) of the questionnaire. Significantly lower scores point out the need for Greek Athletes and coaches to attend relative seminars to reinforce the dual relation-ship between athletes and coaches. Future research should take into account the evaluation of factors such as confidence and self-esteem to gather more information on how to maintain an effective athlete – coach rela-tionship.